Optimalisasi Penentuan Logam Cu(II) Mengunakan Metoda Voltammetri Stripping Adsorptif (VSAd) - Pardi, Hilfi; Willian, Nancy (Al-Kimia, 2021)
Copper is an essential heavy metal, but if in concentrations that pass the threshold and accumulate in the body, it will be toxic which can cause various diseases. One of the methods for determining Cu(II) metal is the Adsorptive stripping voltammetry (VSAd). This research is to determine the metal using voltammetry stripping Adsorptive (VSAd) in samples of river water and sea water. To obtain maximum results in this method, it is necessary to have optimum conditions for various ligands (chalcone, 2,2' Bipyridine, 8-Hydroxyquinoline, Ammonium pyrrolidinedithiocarbamate) for potential accumulation , accumulation time, pH and optimum ligand concentration, as well as determining the accuracy and precision of the method used by determining the relative standard deviation (SDR) value, as well as the recovery value. The results obtained were chalcone as the optimum ligand, the optimum accumulation potential was -0.1 V, the optimum accumulation time was 60 seconds, the optimum solution pH was 6, and the optimum chalcone concentration was 0.5 mM. The relative standard deviation value is 4.27%, the recovery value is 98.31%. The application of the VSAd method to water samples resulted in the concentration of Cu(II) metal in the Batang Air Sidingin Padang river sample, which was 4.778 g/L and the estuary of Padang which was 5.189 g/L.